Health Coaching pada Penderita Hipertensi di Pusat Layanan Kesehatan Primer - Agusta Dian; Yulianah Sulaiman; Nurdin M (Yayasan Inspirasi El Burhani, 2026)
Introduction: Hypertension remains a major global public health problem due to its high prevalence, chronic course, and substantial contribution to cardiovascular morbidity and mortality. Although pharmacological therapy is widely available, long-term blood pressure control remains suboptimal, largely due to inadequate implementation of self-care behaviors. Objective: This community service program aimed to enhance the capacity of patients with hypertension to manage their condition independently through comprehensive and sustainable self-care by integrating health education and health coaching. Method:The program was conducted at Wonomulyo Primary Health Care Center, Polewali Mandar Regency, on January 17, 2026, using a promotive and preventive approach. Implementation was carried out in several stages, including preparation, core activities, and evaluation. Core activities comprised participant registration and blood pressure measurement, hypertension-friendly exercise, interactive self-care education, and structured health coaching sessions. Result: A total of 80 participants were involved, consisting of 40 patients with hypertension and 40 supporting participants. Initial assessments revealed that most hypertensive participants had uncontrolled blood pressure. After the intervention, participants demonstrated improved understanding of hypertension management, increased motivation and self-efficacy, and greater readiness to adopt self-care behaviors. Health coaching facilitated the development of realistic self-care plans, while family and community involvement strengthened social support for sustained behavior change. Conclusion: Integrating self-care education and health coaching within primary health care–based community service effectively empowered patients with hypertension to improve self-management behaviors and shows promise as a sustainable model for hypertension control and health promotion.